Global Scenes of Biblical Injustice Glimpsing the Poor and Oppressed in Today''s World. - Brookman, W. R. (Lanham : University Press of America, 2011)
What do we really know about the ins and outs of the lives of those who exist in a world of extreme poverty or oppression. This thought-provoking book incorporates challenges for a Christian response regarding those whose daily plights fly in the face of what Scripture teaches about justice.
Chapter 11: Thinking, Acting, and Praying Through Global Scenes of Biblical InjusticeAppendix A: United Nations Millennium Declaration; Appendix B: Millennial Development Goals, Target, and Indicators; Bibliography.
Print version record.
Keywords: Poverty; POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; Poverty; Poverty -- Religious aspects -- Christianity; Christianity and justice; Electronic books